Investigation of the role of CD24 gene in the progression of colorectal cancer - Hakami, Zaki (2021)
Cluster of differentiation (CD) 24 is a glycosyl-phosphatidylinositol (GPI) anchor protein. CD24 is a heavily glycosylated protein, containing 16 putative O-glycosylation sites and two putative N-glycosylation sites. In colorectal cancer (CRC) and many other cancers, CD24 induces stemness, cell motility (both migration and invasion) and, through interaction with endothelium, possibly metastasis. The mechanisms by which it exerts these activities are not known. Therefore, this thesis aimed to (i) investigate the role of the putative N-glycosylation sites in mediating CD24 function, (ii) define the signalling pathways and ligands that mediate CRC cell adhesion to endothelium and metastasis, and (iii) delineate CD24 involvement in CRC angiogenesis.